Palladium immobilized on in situ cross-linked chitosan superfine fibers for catalytic application in an aqueous medium. (5th June 2018) - Liang, Lulu; Nie, Li; Jiang, Minjuan; Bie, Fusheng; Shao, Linjun; Qi, Chenze; Zhang, X. Man; Liu, Xuejing
Abstract : Chitosan composite superfine fibers with a diameter of 321 ± 99 nm were prepared by electrospinning with PEO as the co-spinning polymer and itaconic acid as the in situ cross-linking agent. Abstract : Chitosan composite superfine fibers with a diameter of 321 ± 99 nm were prepared by electrospinning with PEO as the co-spinning polymer and itaconic acid as the in situ cross-linking agent. Itaconic acid was homogeneously dispersed in chitosan fibers and the in situ cross-linking endowed the prepared chitosan composite fibers with improved solvent resistance, thermostability and mechanical strength. Palladium species immobilized on these annealed chitosan fibers can efficiently catalyze the reduction reaction of 4-nitrophenol as well as the Mizoroki–Heck reaction of aromatic iodides with n -butyl acrylate in an aqueous medium. Furthermore, the larger fiber structure can facilitate the recovery and reuse of the palladium catalyst. The remarkable catalytic performance and easy recovery make this novel fiber-supported palladium catalyst hold great potential applications in green chemistry.